Jupiter cloud morphology and zonal winds from ground‐based observations before and during Juno's first perijove. Issue 10 (25th May 2017) - Hueso, R.; Sánchez‐Lavega, A.; Iñurrigarro, P.; Rojas, J. F.; Pérez‐Hoyos, S.; Mendikoa, I.; Gómez‐Forrellad, J. M.; Go, C.; Peach, D.; Colas, F.; Vedovato, M.
Abstract: We analyze Jupiter observations between December 2015 and August 2016 in the 0.38–1.7 μm wavelength range from the PlanetCam instrument at the 2.2 m telescope at Calar Alto Observatory and in the optical range by amateur observers contributing to the Planetary Virtual Observatory Laboratory. Over this time Jupiter was in a quiescent state without notable disturbances. Analysis of ground‐based images and Hubble Space Telescope observations in February 2016 allowed the retrieval of mean zonal winds from −74.5° to +73.2°. These winds did not change over 2016 or when compared with winds from previous years with the sole exception of intense zonal winds at the North Temperate Belt. We also present results concerning the major wave systems in the North Equatorial Belt and in the upper polar hazes visible in methane absorption bands, a description of the planet's overall cloud morphology and observations of Jupiter hours before Juno's orbit insertion. Plain Language Summary: We present a characterization of Jupiter clouds and their dynamics prior to Juno's arrival. We present results based on observations with our own high‐resolution instrument PlanetCam, Hubble Space Telescope images acquired in February 2016, and analysis of high‐quality images provided by amateur astronomers using small telescopes. Before Juno's arrival to Jupiter its atmosphere behaved in a normal way without major convective outbreaks or changes in its usual belts and bands. Juno's first perijove characterized Jupiter at a time of usual behavior of the planet. Zonal winds were similar to previous years except for high values of the wind velocity at the most intense jet stream in the planet in the North Temperate latitudes which reached values of 157 m/s. We also study two systems of planetary‐scale waves in the planet: The first system is north to the equator in the North Equatorial Belt and is characterized by a regular pattern of large dark features in the planet. These are regions of reduced cloud content formed by an atmospheric wave. The second system is an undulatory pattern in the polar hazes that is best observed in the southern hemisphere. Both are characterized for later comparisons with results from the Juno mission. Key Points: We present the overall cloud morphology of Jupiter over 2016 from images in the spectral range 0.38–1.7 micrometers We characterize the equatorial hot spots and present snapshots of the polar regions providing context for observations from Juno We measured zonal winds from December 2015 to June 2016 spanning the latitude range 74.5°S–73.2°N without variability over this period